La gestión de calidad como estrategia para incrementar las ventas en la empresa DLG MODAS SAC, ciudad de Trujillo, 2019 - Terrones Abanto, Miguel Angel (2021)
The main objective of this thesis was to determine the relationship between quality management as a strategy in the sales of the company to be studied. The present investigation is of descriptive correlational type. The sample consisted of 178 employees of the company; the data collection techniques were the survey, the interview, the observation and the documentary analysis (report 2019). The formulated research problem was: What is the relationship between quality management and sales of the company DLG MODAS SAC of the city of Trujillo 2019? The validity of the proposed hypothesis was demonstrated, thanks to the results obtained, which in turn allowed the discussion "The relationship between quality management and sales of the company DLG MODAS SAC of the city of Trujillo 2019 is direct and significant." According to the results, it was concluded that: there is a relationship between the level of quality management and customer sales in the company DLG Modas Sac. of the city of Trujillo 2019, through the chi square statistical test with p = 0.000